Progress in ovarian cancer research: Proceedings of the 5th Biennial Ovarian Cancer Research Symposium. Issue 2 (1st March 2006) - Disis, M. L.; Rivkin, S. E.; Baron, A.; Markman, M.; Connolly, D.; Ueland, F.; Kohn, E.; Trimble, E.; Berek, J. S.
Abstract : Ovarian cancer remains the most lethal gynecological malignancy. The 5th Biennial Symposium overviewed the progress of ovarian cancer research over the last few years. Molecularly based technologies have allowed the identification of multiple biomarkers to aid in ovarian cancer diagnosis and treatment. Furthermore, data analysis systems evaluating the behavior of these markers have been designed. Therapeutic use of ovarian cancer protein markers has been fueled by the development of animal models that more closely simulate the pathogenesis of ovarian cancer, and multiple new therapies are being developed that may have impact against the disease. Finally, the design of clinical trials both for ovarian cancer treatment and prevention are key in advancing the science of ovarian cancer into the clinic. The need for strategies that would optimize patient participation in clinical trials is paramount.